1970
DOI: 10.1029/wr006i005p01253
|View full text |Cite
|
Sign up to set email alerts
|

Demand for Water under Dynamic Conditions

Abstract: An empirical analysis of the effects on residential water use of changing from a flat rate price structure to a metered one is presented. Time series data, for the first time, are used to study the dynamics of residential water demand. The results include the observations that: (1) sprinkling demands were reduced by the introduction of meters, with actual sprinkling being greater than the calculated ideal under flat rates and less than ideal under metered rates; (2) sprinkling use not only declined with the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

1971
1971
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 4 publications
(2 reference statements)
0
18
0
1
Order By: Relevance
“…For example, linear speci cation was used by Hanke (1970), Young (1973) and many other researchers. Log linear models were used by Young (1973), Danielson (1979) and Nieswiadomy (1992).…”
Section: Model Estimation and Resultsmentioning
confidence: 99%
“…For example, linear speci cation was used by Hanke (1970), Young (1973) and many other researchers. Log linear models were used by Young (1973), Danielson (1979) and Nieswiadomy (1992).…”
Section: Model Estimation and Resultsmentioning
confidence: 99%
“…8 Several studies found that the transition from flat rates to metering in Denver had almost no effect on inhome water use (Brown & Caldwell, 1984). Hanke (1970), however, found a 36% reduction in in-home use after Boulder, Colorado, switched to metering. A drawback of this literature for our purposes is that it focuses on single-family dwellings.…”
Section: Short-term Versus Long-term Impactsmentioning
confidence: 89%
“…Grossman et al (1993, p. 159, n. 16) cite the result of Hanke (1970) where water consumption in Boulder, Colorado, was found to decrease after the replacement of a fixed charge by a metered pricing structure. They suggest that, 'though Hanke did not suggest free-rider behaviour as an explanation for the observed phenomenon, it is a consistent explanation'.…”
Section: Endnotesmentioning
confidence: 94%